Dictionary of ecology and the environment - Collin, P. H. (Peter Hodgson) (London Peter Collin Pub., 2001)
This little dictionary of 8,500 entries includes pronunciation and definition but not derivation or usage examples. One unique feature is the frequent concise comment or quote at the end of an entry such as this comment from Green Magazine at the entry, incident: "Water pollution incidents more than doubled in England and Wales during the Eighties." As with this example, comments or quotes usually refer to the UK context. Includes appendices such as a chronology of recent natural disasters. Distributed by Independent Publishers Group. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Ecology -- Dictionaries. Environmental sciences -- Dictionaries. Ecology -- dictionaries